Biological nitrogen removal under inhibitory conditions in a sequencing batch reactor - Karn, Sunil Kumar; Annachhatre, Ajit P.; Dahl-Madsen, Karl Iver; Kim Oanh, N. T.; Government of Denmark (DANIDA) (Bangkok : Asian Institute of Technology, 1998)
This study was carried out to investigate the nitrogen removal from wastewater under inhibitory conditions using Sequencing Batch Reactor (SBR). Synthetic wastewater containing aniline was used as feed. A 40-liter laboratory scale SBR was operated with aniline containing synthetic wastewater during the entire investigation. Aniline concentration in the feed was increased gradually from 100 to 450 mg/l while the total cycle time of the SBR was reduced from 12 hours to 8 hours. The cycle time was optimized by reducing the time of react phase of the cycle. Performance of the reactor was observed at different react phases ranging from 9 hours (3 hours aerobic and 6 hours anoxic) to 3.75 hours (1.75 hours aerobic and 2 hours anoxic). The optimal react time was achieved at 4.75 hours (2.25 hours aerobic and 2.5 hours anoxic). At this period, removal of aniline, COD and total nitrogen was observed more than 98%, 95% and 85% respectively for the feed aniline concentrations up to 450 mg/I. The average rate of reaction during aerobic and anoxic phases for aniline biodegradation, nitrification and denitrification were found as 20-40, 2-4 and 1.5-4.0 mg/gVSS/hr respectively. Profiles of pH, DO and ORP during the react phase were successfully simulated to indicate the specific process changes as the start and end of nitrification and denitrification processes. The effect of inhibition due to aniline was observed during the nitrification process. Conversion of NH4 + to N0 2- by Nitrosomonas was not initiated until the concentration of aniline inside the reactor had dropped below 4-5 mg/I. Similarly, conversion ofN02- into N03- by Nitrobacter was inhibited when the concentration of aniline in the feed was reached to about 400 mg/I. Furthermore, as the concentration of aniline in the feed was increased over 450 mg/I, the conversion of N02- into N03- had almost ceased. Nitrobacter activity could not be revived even after aniline concentration in feed was reduced to 300 mg/I. However, there was no significant loss in the total nitrogen removal efficiency of the SBR due to the effects of inhibition as N02- produced by Nitrosomonas could still be denitrified under anoxic condition.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Sewage -- Purification -- Nitrogen removal